Photo-crosslinked bioactive BG/BMSCs@GelMA hydrogels for bone-defect repairs - Yufeng Ai; Fang Dai; Wenfeng Li; Fancheng Xu; Hanwen Yang; Jianxin Wu; Kaiqiang Yang; Li Li; Fanrong Ai; Li Song (Materials Today Bio, 2023)
The clinical treatments of bone defects remain a challenge. Hydrogels containing bone marrow mesenchymal stem cells (BMSCs) are extensively used to bone regeneration because of excellent biocompatibility and hydrophilicity. However, the insufficient osteo-induction capacity of the BMSC-loaded hydrogels limits their clinical applications. In this study, bio-active glass (BG) and BMSCs were combined with gelatin methacryloyl (GelMA) to fabricate composite hydrogels via photo-crosslinking, and the regulation of bone regeneration was investigated. In vitro experiments showed that the BG/BMSCs@GelMA hydrogel had excellent cytocompatibility and promoted osteogenic differentiation in BMSCs. Furthermore, the BG/BMSCs@GelMA hydrogel was injected into critical-sized calvarial defects, and the results further confirmed its excellent angiogenetic and bone regeneration capacity. In addition, BG/BMSCs@GelMA promoted the polarization of macrophages towards the M2 phenotype. In summary, this novel composite hydrogel demonstrated remarkable potential for application in bone regeneration due to its immunomodulatory, excellent angiogenetic as well as osteo-induction capacity.